Local structures of Ca, Ti and Fe in meteorite fusion crusts. (May 2016) - Tobase, T; Yoshiasa, A; Hiratoko, T; Hongu, H; Isobe, H; Nakatsuka, A; Arima, H; Sugiyama, K
Abstract: The local structures of meteorite fusion crusts were studied by Ca, Ti and Fe K-edge XANES and EXAFS spectroscopy. The surface of meteorites were melted and volatilized with extreme high temperature and large temperature gradient when meteorites were rushed into atmosphere. This study indicated that meteorite fusion crusts have unique local structures. The local structures of fusion crusts differ from tektites especially in intensity of the shoulder in the rising flank of the edge in Ca XANES spectra. It is consistent with chemical composition change by the volatilization of Si at fusion during atmospheric entry. The high estimated Fe 3+ / (Fe 2+ +Fe 3+ ) ratio in meteorite fusion crusts indicates that meteorite fusion crusts are formed into atmospheric oxidation condition. The Ca-O distances in meteorite fusion crusts are 2.612.66 A and are extremely longer than in other natural glasses. The fusion crusts have unique local structure since they experienced extremely high temperature and short quenching time. The XAFS method is effective in distinction of meteorite fusion crusts and classification of natural glass.